Flexible Radio: A Framework for Optimized Multimodal Operation via Dynamic Signal Design. Issue 3 (1st August 2005) - Dagres, Ioannis; Zalonis, Andreas; Dimitriou, Nikos; Nikitopoulos, Konstantinos; Polydoros, Andreas
Abstract : The increasing need for multimodal terminals that adjust their configuration on the fly in order to meet the required quality of service (QoS), under various channel/system scenarios, creates the need for flexible architectures that are capable of performing such actions. The paper focuses on the concept of flexible/reconfigurable radio systems and especially on the elements of flexibility residing in the PHYsical layer (PHY). It introduces the various ways in which a reconfigurable transceiver can be used to provide multistandard capabilities, channel adaptivity, and user/service personalization. It describes specific tools developed within two IST projects aiming at such flexible transceiver architectures. Finally, a specific example of a mode-selection algorithmic architecture is presented which incorporates all the proposed tools and, therefore, illustrates a baseband flexibility mechanism.